Optimization of Production Scheduling to Minimize Makespan in the 54-Ton Flat Carriage Project at PT INKA Multi Solusi: Using the Nawaz, Enscore, and Ham (NEH) Method and A Case Study on the Application of Scheduling Optimization in Manufacturing - Wilda, Erina Mu’rivatul; Sumiati (Journal Knowledge Industrial Engineering (JKIE), 2025)
Efficient production scheduling is essential to achieve optimal operational goals in the manufacturing industry. This study aims to optimize production scheduling on a 54 Ton Flat Carriage manufacturing project at PT INKA Multi Solusi using the Nawaz, Enscore, and Ham (NEH) Method. The main focus of this study is to minimize the total completion time (makespan) in order to improve operational efficiency, reduce costs, and meet deadlines and quality standards that have been set. The NEH method is applied to compare the results with the method commonly used by the company, namely First Come First Serve (FCFS). The results show that the NEH method produces a smaller makespan (1.39 hours) compared to the FCFS method which produces a makespan of 1.41 hours. Thus, the NEH method is proven to be more efficient in reducing makespan and can be used as a reference for better production scheduling. This study also contributes to the allocation of limited resources such as machines, labor, and raw materials, in order to increase the company's productivity and competitiveness amidst the tight competition in the manufacturing industry